Empowered or entangled: Agency and choice in women$1 (Bs employment in Indias - Neetha, N. (South Asian Survey)
In India, formation of NGO-aided self-help groups (SHGs) for production was seen as an important step to lift women out of economic marginalisation and, thus, for women$1 (Bs empowerment. With changes in economic policies, challenges of wage employment for women were also assumed to have been addressed. In this context, this article, drawing from the history of empowerment discourse and its obsession with the economic aspect, examines women$1 (Bs employment and its multiple dimensions The analysis provides insights into the gender-based inequalities in the labour market which are evident in the concentration of women workers in precariat, feminised jobs either under the control of the family or without any recognition or legal protection. The prevalence of regressive gendered ideologies in employment and in the division of housework raises critical questions about the understanding of the two critical pillars of empowerment, namely, choice and agency.- Reproduced s
Keywords: Culture, Global economy, History, International affairs, International relations